ACTIVITIES OF LAW ENFORCEMENT ORGANIZATIONS DURING IMPLEMENTATION OF THE PROTECTION OF SOCIALIST PROPERTY LAW - Sagnaikyzy, Samal (Вестник ЗКУ, 2023)
It is known that against the background of the Red Terror in 1931-1932, Kazakhstan was gripped by mass famine, and the condition of the population was severe. People tried to find a way out of the impasse, thinking about how not to die of hunger. The campaign to protect socialist property, which began in 1927-1928, along with campaigns to destroy the rich, and harvest grain and meat, also caused great stress among the population. Hungry naubats pushed the population to sign state property. During this campaign, Soviet human rights organizations were active and allowed various exaggerations. Even those who carried out this campaign became subordinates of the administrative command system. Law enforcement and administrative organizations also overstepped their authority during this campaign, and violated human rights during the execution of orders from the Communist Party. If we take into account that the common people were mainly on the side of the thieves of socialist property, then at first this contradicts the Bolsheviks' concept that "Soviet human rights organizations protect the interests of the common people." In the course of the research, I reveal in detail the activities of law enforcement organizations during the campaign to protect socialist property.